Screening Internet websites for educational potential in undergraduate medical education. - Burd, Andrew (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
This paper addresses the difficulty of finding suitable websites to support undergraduate medical students in learning key concepts and skills in plastic surgery in particular and other areas of undergraduate medical education in general. Based on a model of the pedagogical elements contained in educational websites, the authors developed a short objective scoring system with five criteria. Pre-university students were used to find websites in plastic surgery. One hundred and fifty of thost that were still in place after a year were evaluated using the objective scoring system. Sixty of these were then selected and were subjectively evaluated by final year medical students in terms of their perceived educational potential. There was only a moderate correlation between the objective and subjective scores. Our conclusion is that it does not seem possible to construct any objective system of medical website evaluation. The discussion of the results of this study focuses on the issues involved in finding suitable web-based material and the diversity between students. New strategies such as formally organized consortia involving agreements between medical schools may evolve.